Kaiju no. 8. 2 - Matsumoto, Naoya (VIZ Media, LLC, 2022)
"With the highest kaiju-emergence rates in the world, Japan is no stranger to attack by deadly monsters. Enter the Japan Defense Force, a military organization tasked with the neutralization of kaiju. Kafka Hibino, a kaiju-corpse cleanup man, has always dreamed of joining the force. But when he gets another shot at achieving his childhood dream, he undergoes an unexpected transformation. How can he fight kaiju now that he's become one himself?! The final test of the Defense Force has come to an end, but the examinees' challenges aren't over yet. A mysterious humanoid kaiju revives a neutralized honju and sics it on Kikoru Shinomiya. Just when Kikoru seems to be at the end of her rope, Kafka rushes to her defense! But what is the humanoid kaiju's goal?"--Amazon.